PENGAWASAN PEMERINTAH DAERAH KABUPATEN KAMPAR DALAM MENANGANI PENAMBANGAN LIAR BATU GUNUNG DI DESA MERANGIN KECAMATAN KUOK KABUPATEN KAMPAR - Endow Muqni; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Background Issue In Illegal Mining That Occurred In The Village Merangin Are Frequent Landslides That Disrupt The Flow Of Traffic And Environmental Damage Will Occur. This Is Caused By The Illegal Miners Who Do Not Have Permission To Mine A Location That Complies With Government Regulations No. 09 Of 2008 On Mining Processed. The Purpose Of This Study Is The First To Analyze The Kampar District Government Oversight In Dealing With Illegal Mining In Rural Districts Merangin Kuok Kampar District. 2 To Analyze The Obstacles In The Implementation Of The Supervision And Control Of Illegal Miners In The Mountain Stone Village Districts Merangin Kuok Kampar District. This Research Is Done With Qualitative Approach With Descriptive Type. Informants Selected As The Information And Data Collected By Interview And Search Of Documents As Research Data.Based On The Results Of The Analysis Conducted By The Author, The Author Can Draw The Conclusion That Government Oversight Of Kampar District In Tackling Illegal Mining Rock In The Mountain Village Of Kampar Regency Merangin Districts Kuok Still Not Implemented, Because The Lack Of Effort Made By The Government So That The Miners Are Still Active Mine.Keywords : Government Oversight.